Análisis de sostenibilidad y competitividad de las empresas turísticas de ocio y recreación del cantón Latacunga, provincia de Cotopaxi. - Rodríguez Suárez, Paula Alejandra (2023)
It was made a sustainability and competitiveness variables analysis in the leisure and recreation touristic enterprises from Latacunga canton, Cotopaxi province, what are registered in the national land register, due to the low demand, which exists in the use these tourist spaces and the disinterest by the authorities’ part into the promoting same ones. The research approach is quantitative, since was used statistical methods, also, it was used the descriptive method for getting conclusions about the sustainability and competitiveness index. The research was complied, through the InnovaRSE and BID methodologies, once, it was achieved the data from the enterprises, it was effected a statistical test in the SPSS software, the same, which is interpreted as do not exist a significant correlation in the sustainability and competitiveness variables. In the enterprises statistical results, it was got, what the sustainability index is 2.22, which is found in a very low range and its parameters are assigned to the planning phase, what shows that the enterprises organization does not provide a lot of attention to subject, due to its ignorance in RSE (Corporate Social Responsibility). Like the other variable, it got a 10,59% index that likes to mean, which it is found in the very low competitiveness range, due to the fact, which they do not have tourist demand and are family businesses. In the order for enterprises improve it was made an exhaustive study, through a FODA analysis, which was divided into MEFI and MEFE matrices, that allowed to use the crossed FODA and in this way, it was created 15 strategies, being all, they are important for the 9 enterprises, and it should start with a strategic plan creation, what involves the organization and business structure, this way, it will help to have not only corporate responsibility, but also sustainable and competitive practices, so that enterprises excel in the touristic market.